Fostering critical thinking: Designing problem-based learning student worksheet on environmental change topic - Nurul Fadilah; S. Suhartini; Suyitno Aloysius (University of Muhammadiyah Malang, 2024)
The growing awareness of the increasingly complex environmental changes requires an educational approach that fosters critical thinking. Through the implementation of PBL, students will gain a deeper understanding and develop an attitude of environmental care, particularly towards their surroundings. This study aims to evaluate the effectiveness of PBL-based student worksheets on environmental change material to train critical thinking skills based on the completeness of learning outcomes and student responses. This research employs the 4D model of development, encompassing the stages of defining, designing, developing, and disseminating. Nonetheless, this study is confined to the third stage of development. The validation used includes material validation media validation. The data at the development stage is sourced from expert validators and subsequently analyzed using the descriptive analysis method. The validation results affirm that the developed worksheet is deemed suitable for implementation. Therefore, it is highly recommended to implement the learning process using this worksheet. Its utilization can significantly contribute to fostering student competency levels. Furthermore, disseminating its benefits widely would further amplify its positive impact across various educational settings.